GLP 1 RECEPTOR AGONISTS AND THEIR EFFECTS ON REWARD AND COMPULSIVE BEHAVIORS - Pieńkowska, Anita; Malon, Paulina; Śliwa, Karol; Trojańska, Aleksandra; Geworkian, Nel; Hariasz, Natalia; Pietz, Martyna; Szymańska, Anita (International Journal of Innovative Technologies in Social Science, 2026)
Background: Addiction and compulsive behaviors are widespread challenges that affect both individual and societal well-being. These behaviors involve persistent engagement in rewarding stimuli despite negative consequences. Glucagon-like peptide-1 (GLP‑1) receptor agonists, initially developed for metabolic disorders, have been shown to modulate neural circuits involved in reward, motivation, and compulsive behavior. Methods: To explore these questions, this review synthesizes evidence from animal studies, mechanistic neurobiological research, neuroimaging, and emerging human trials. The focus is on the effects of GLP‑1 receptor activation on reward processing, motivation, and compulsive behaviors. Results: Preclinical studies indicate that GLP‑1 receptor agonists reduce drug- and food-related reward seeking, suppress relapse-like behavior, and modulate phasic dopamine signaling in mesolimbic circuits. Neurochemical and electrophysiological studies demonstrate coordinated activity between dopaminergic and inhibitory neurons. In humans, early trials suggest GLP‑1 receptor agonists can reduce alcohol consumption and craving, and observational data hint at broader effects on other reward-related behaviors. Conclusion: GLP‑1 receptor signaling modulates central motivation and reduces maladaptive reward-seeking. These findings suggest GLP‑1 receptor agonists have therapeutic potential for compulsive behaviors and addiction, relevant to behavioral science, psychiatry, and public health.